A Symmetrical Fractal-based Balanced Branch-Line Coupler for Simultaneous Low- and Mid-band 5G Frequencies Applications - Shallah, Abdulkadir B.; Zubir, Farid; Rahim, Mohamad Kamal A.; Yusoff, Zubaida (Applied Computational Electromagnetics Society Journal (ACES), 2023)
Symmetry is a key factor for Branch-Line Couplers (BLCs) in RF and microwave systems. This balanced approach evenly distributes power between two output ports, aiding impedance matching and reducing unwanted coupling and crosstalk, while increasing input-output isolation. Furthermore, the symmetrical design of BLCs ensures favorable return loss and phase balance, which are essential for phase-sensitive detectors and beamforming. This symmetry also guarantees consistent performance over a wide frequency range, making it suitable for broadband or multi-frequency applications. We present a compact BLC operating in two frequency bands, ideal for 5G sub-6 GHz applications. It uses T-shaped lines with folded lines and stubs in a Minkowski fractal shape, resulting in a size reduction of 90%. The design and simulation were performed using the CST Microwave Studio at 0.7 GHz and 3.5 GHz, achieving a new high frequency band ratio of 5. A prototype on Rogers RT5880 substrate (εr=2.2,h=0.787 mm) was tested to validate the design’s effectiveness, offering potential for modern wireless applications requiring versatile frequency band operation.